Severe farmer's lung following a workplace challenge. - Kokkarinen, J.; Tukiainen, H.; Terho, Erkki O. (Scandinavian Journal of Work, Environment & Health, 1992)
A severe attack of farmer's lung developed in a dairy farmer after a workplace challenge. The patient showed full recovery after corticosteroid therapy. If a workplace challenge is considered necessary in the diagnosis of farmer's lung, care should be taken to avoid unnecessarily heavy exposure to the offending antigens.